The Influence of Content Marketing in Efforts To Improve Firm Performance of Msmes in Purworejo District, Moderated By Price Strategy and Customer Relationship Management - Ivan Fatchan Gani Wardana; Alimuddin Rizal (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to examine the influence of marketing content on business performance with moderation in price strategy and CRM. This research design is quantitative research with primary data in the form of the calculation of assets, turnover, and capital owned by MSMEs in Purworejo Regency. The data collection technique uses library research and documentation techniques. The population in this study is MSMEs that are members of the Purworejo Regency MSME Forum in 2025, amounting to 1,819 business actors. The sampling technique used is the Slovin formula so that the sample for this study is 67 business actors. The results of the study show that marketing content and CRM have an impact on business performance, Price Strategy has no impact on business performance and both price strategy and CRM strengthen the relationship between marketing content and business performance. Future studies may explore the deeper dynamics of these variables in other regions or sectors to gain further insights into effective business management practices.